圆光栅测量齿轮传动系统回转精度 - 徐毓娴; 白立芬; 于水; 李庆祥 (Jixie chuandong)
This paper discribed the principle and structure of the gear transmission error measurment using circle grating. The retarding gear trasmission eroor （ i =15） was measumed. The measurment result was coincided with the theoretical analysis. Thes method is compact and reliable. It can be used in a wide field.